Pendidikan Karakter: Konsep dan Implementasinya Dalam Pembelajaran di Sekolah/Madrasah - Muzhoffar Akhwan (EL-TARBAWI, 2014)
Education is a medium to achieve values and meaning of life, rather than quantitative-artificial values. The true educatoin will help people to earn meaning for everything they learn all along education process. Meaning achievement is the main objective of learning process. There is no education when people do not achieve meaning through their education process. Many scholars found that, this circumstance may result from the lack of character building on education in the schools. However, character building education needs a good-spesific system that at least includes course details, tools teaching, methods, etc. Furthermore, this paper proposes learning methods that can be applied or further researched by teachers or scholars. Those methods are: 1) role model method; 2) habitual method; and 3) reward and punishment method.